Effective Classroom Management Strategies to Improve Student Discipline - Rizka Nabila; Achmat Mubarok; Wiwin Fachrudin Yusuf; Muhammada (Journal of Educational Management Research, 2026)
This study aims to analyze classroom management strategies implemented by teachers to improve student discipline during the learning process. The research employed a qualitative approach using a case study design to gain an in-depth understanding of classroom management practices. Data were collected through observations, semi-structured interviews, and documentation involving school principals, teachers, student affairs staff, and students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation, method triangulation, and member checking. The findings revealed that classroom management strategies significantly contributed to improving student discipline by establishing classroom rules, providing supervision, motivating students, and applying interpersonal approaches to create an orderly and conducive learning environment. Effective classroom management was supported by teacher consistency, assertiveness, and humanistic communication. Preventive approaches through guidance and motivation before learning activities also strengthened students’ awareness of discipline. However, several challenges were identified, including differences in student characteristics, inconsistent rule implementation among teachers, and peer environmental influences. The study implies that effective classroom management requires a balance between disciplinary enforcement and persuasive-communicative approaches to foster positive student behavior and support successful learning outcomes.